Літературне життя на Волині в 1920-1930-ті роки: суспільно-політичні умови, угруповання, персоналії - Понєдєльник, Л. (Краєзнавство, 2019)
У статті розкрито діяльність представників письменницької творчої інтелігенції Волині міжвоєнного періоду (1921–1939 рр.). Проаналізовано культурну політику польської влади у Волинському воєводстві Другої Речі Посполитої, показано вплив суспільно-політичного процесу на розвиток літератури.
Розкрито маловідомі біографії волинських письменників, показано їх внесок в українську та світову
літературу, висвітлено активність письменників націоналістичної, пролетарської, романтично-ліричної течій та їхнє ставлення до правлячої політичної системи. Виявлено особливості літературного руху етноменшин регіону. The literary life of the Volyn Voivodeship in 1921–1939 was is researched. The cultural policy of the Polish
authorities in Volyn is analyzed together with the influence of the socio-political process on the development
of literature. The biographies of the Volyn creative people are represented, the contribution of representatives
of national literature in Ukrainian and world art, the activity of writers of the proletarian current and their attitude
to the ruling social system are shown.
Volyn writers actualized socio-political, socio-economic, cultural and education problems of interwar
Volyn. The peculiarities of the literary movement of the of the region are discovered.As an example of the interethnic
contacts, it is also shown the activity of the union «Volyn» which united the talented Polish and Ukrainian
writers.
The peculiarities of the literary movement of the of the region are discovered. There is also analyzed the
influence of the church on the creative work of writers, on the lyrical trend of , obtaining the political coloring
of literary people. As an example of the interethnic contacts, it is also shown the activity of the union «Volyn»
which united the talented Polish and Ukrainian writers. We analyzed the activity of publishing houses and
bookstores which published and disseminated press issues and literature. Ukrainian publishing houses were
under a permanent pressure.
At various stages of the article preparation, a set of general scientific, interdisciplinary, specialhistorical
methods was used: analysis and synthesis, comparative-historical, structural-functional, problem-
chronological, biographical and others. Their essence and features of rational-combined application
are clarified.